Inovasi Pendidikan Berbasis Industri Kreatif Akademik Perguruan Tinggi dengan Sistem Teknologi Komunikasi dan Informasi untuk Peningkatan Ekonomi - Rahmini Hadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: The issue unemployment of college graduates each year increased. This indicates the education patterns at universities need a new innovation to solve this problem. One of them through innovation in education based on academic creative indutries in university by using technologization of communication and information. Thus academic creative industries are educational activities which are managed such as insdustry to produce something. Product that is represented the development of science and society problematic solution. The creation and distribution of products made the technologization based on communication and information so that the creation of products in accordance with the field of science and people then there will be an increase in profit and the existence of institutions and professional college graduates and then it will be accepted in the work world after gradution. Its impact, it will be any increasing in society economy that is using the products as well as graduates who were employed, so it would create economic impact in society. Keyword: Creative Industries, Products, Academic, University, Communication Technology and Informatics.